Two-dimensional modeling of torrefaction of a large biomass particle. Issue 13 (21st October 2017) - Kamila, Biswajit; Sadhukhan, Anup Kumar; Gupta, Parthapratim; Basu, Prabir; Regmi, Bharat; Dutta, Animesh; Acharya, Bishnu
ABSTRACT: A two-dimensional (2-D) model is developed to predict the torrefaction behavior of a large wet biomass particle. Although one-dimensional (1-D) model is found to be adequate for L / D  ≥ 6, the necessity of using 2-D model at lower L/D ratios and higher torrefaction temperature is established. Errors up to 18% are observed in predicted mass fractions between 1-D and 2-D models. The center temperatures differed more, up to 96%, between z =  0 and z = L /2 in 2-D model which is not captured by the 1-D model. The model predictions agree well with the experimental results of the present authors and others. The evolution of the temperature profile is found to govern the mass fraction profile. At higher reactor temperature, three distinct zones are visible in the contour plots: peripheral fully torrefied zone, intermediate torrefying zone, and core with unreacted virgin biomass zone. Simulation studies show the formation of two symmetric annular hot spots at the ends, which move inward axially and subsequently merge at the center, the rate being faster for smaller L / D ratio. However, 1-D model does not provide such insight. The effects of reactor temperature, particle size, the residence time, and the initial moisture content on the torrefaction behavior are investigated.